Self-Efficacy and its Relation to the Cognitive Assessment for the Daily Disturbances for the University of Baghdad Students (Journal of the College of Education for Women, 2019)
The current research tackles the self-efficacy and its relation to the cognitive assessment for the daily disturbances for the University of Baghdad students. Two criteria have been adopted to achieve the objectives of the research. The sample of this study consists of 200 male and female students who were chosen randomly. The data were analyzed statistically, revealing that the university students owned their own self-efficacy as well as a cognitive assessment for the daily disturbances and they recognized them as self-threatening. The results also indicated the existence of a prediction activity in the field of the cognitive assessment to the daily disturbances selection. In light of the acquired results, the study recommends the necessity of developing guidance programs in the colleges to help students overcome the educational, social and psychological problems they confront.